2020
DOI: 10.1039/d0nh00333f
|View full text |Cite
|
Sign up to set email alerts
|

The biomolecule corona of lipid nanoparticles contains circulating cell-free DNA

Abstract: The biomolecule corona spontaneously adsorbed onto lipid-based nanoparticles (NPs), upon incubation with human plasma, contains circulating cell-free DNA (cfDNA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 70 publications
(115 reference statements)
0
22
0
Order By: Relevance
“…The physicochemical characteristics of the liposomes employed are summarized in Figure e. Corona-coated liposomes were purified from any unbound plasma components by a two-step purification protocol which is based on size exclusion chromatography followed by membrane ultrafiltration, as previously extensively optimized and described. ,,,, This protocol has been previously shown to completely eliminate unbound proteins and to result in a reproducible composition of protein corona . The resultant purified in vivo protein coronas at the three different time points were comprehensively characterized and compared (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…The physicochemical characteristics of the liposomes employed are summarized in Figure e. Corona-coated liposomes were purified from any unbound plasma components by a two-step purification protocol which is based on size exclusion chromatography followed by membrane ultrafiltration, as previously extensively optimized and described. ,,,, This protocol has been previously shown to completely eliminate unbound proteins and to result in a reproducible composition of protein corona . The resultant purified in vivo protein coronas at the three different time points were comprehensively characterized and compared (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…The elevations of a protein, lipid, and nucleic acid in the PEG-GNP deposited regions are supposed to associate with biomolecule adsorption, immune response, alteration of gene, protein expression, and metabolism induced by GNP administration. , The serum protein adsorption on PEG-GNPs may contribute to the increase in protein content in the deposited sites. Recently, several evidence suggest that lipids, nucleic acids, and metabolites can also interact with the surface of NPs . In our previous research, we found PEG-GNPs to mainly deposit in the liver and could subsequently induce the elevation of gene expression of drug-metabolizing enzymes including cytochrome P450 (CYP450) isoforms, phase II metabolized enzymes UDP-glucuronosyltransferases (UGT), and drug uptake and efflux transporters including P-glycoprotein (P-gp), organic cation transporter 1 (OCT1), and organic anion transporters (OATs) after i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EV isolates often contain lipoproteins, protein aggregates, and nonvesicle macromolecules (Sunkara et al, 2016). We also know that cell-free DNA can adsorb to lipid nanoparticles (Gardner et al, 2020), which is likely to occur for circulating EVs too, but surprisingly, this phenomenon is largely overlooked in the field. These "contaminants" influence the biological function Abbreviations: AFM, atomic force microscopy; AFM-IR, atomic force microscope infrared-spectroscopy; CMSC29, chorionic mesenchymal stromal/stem cell line; CEVs, extracellular vesicles derived from chorionic mesenchymal stromal/stem cell; DMSC23, decidual mesenchymal stromal/stem cell line; DEVs, extracellular vesicles derived from decidual mesenchymal stromal/stem cell; EVs, extracellular vesicles; HBSS(-), Hank's balanced salt solution; LPS, lipopolysaccharide; MSC, mesenchymal stromal/stem cell; PTA, particle tracking analysis; nFCM, nanoflow cytometry; RMM, resonant mass measurement; TRPS, tunable resistive pulse sensing; TFF, tangential flow filtration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EV isolates often contain lipoproteins, protein aggregates, and non-vesicle macromolecules ( Sunkara et al, 2016 ). We also know that cell-free DNA can adsorb to lipid nanoparticles ( Gardner et al, 2020 ), which is likely to occur for circulating EVs too, but surprisingly, this phenomenon is largely overlooked in the field. These “contaminants” influence the biological function of EVs and are not trivial to detect due to the sensitivity of experimental methods.…”
Section: Introductionmentioning
confidence: 99%